In Defense of an Account of Degrees of Epistemic Responsibility (Philosophy and Progress, 2024)
This article explores the concept of degrees of epistemic responsibility by examining the debate between Michael Bishop and Katherine Puddifoot on the internalist perspective on epistemic responsibility. While Bishop’s empirical evidence challenges internalism, Puddifoot argues it can be supportive. The author presents an account of degrees of epistemic responsibility, drawing inspiration from Martin Montminy’s idea of moral responsibility. The central argument suggests that an agent is epistemically responsible only if her reasoning strategy aligns with her epistemic abilities, a concept referred to as epistemic par performance. The paper discusses how the Bishop-Puddifoot debate contributes to this perspective, presents Montminy’s view on moral responsibility, and applies it to epistemic responsibility, emphasizing the importance of matching reasoning strategies with individual abilities. The article ultimately highlights the contextual, ability-dependent, and effort-inclusive nature of epistemic responsibility and offers a framework to recognize and credit agents based on their contributions and endeavors in expanding our epistemic horizons.Philosophy and Progress, Vol#73-74; No#1-2; Jan-Dec 2023 P 95-112